2010
DOI: 10.2471/blt.09.064709
|View full text |Cite
|
Sign up to set email alerts
|

Trends in smoking and quitting in China from 1993 to 2003: National Health Service Survey data

Abstract: Objective China has around 350 million smokers, more commonly men. Using data from National Health Service Surveys conducted in 1993, 1998 and 2003, we (i) estimated trends in smoking prevalence and cessation according to sociodemographic variables and (ii) analysed cessation rates, quitting intentions, reasons for quitting and reasons for relapsing.Methods Data were collected from approximately 57 000 households and 200 000 individuals in each survey year. Household members > 15 years of age were interviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(95 citation statements)
references
References 43 publications
5
87
3
Order By: Relevance
“…A national study on smoking behaviour conducted in 1996 found that smokers' self-reported health status, health concern, family opinions, as well as education and financial status were associated with their quitting behaviour 28 29. These are similar to the recent findings from the National Health Service Surveys 30. Two studies conducted among medical workers, teachers, factory workers and secondary students in Hong Kong and mainland China found that being male, married and having high quitting self-efficacy were associated with the intention to quit smoking 31 32.…”
Section: Introductionsupporting
confidence: 73%
“…A national study on smoking behaviour conducted in 1996 found that smokers' self-reported health status, health concern, family opinions, as well as education and financial status were associated with their quitting behaviour 28 29. These are similar to the recent findings from the National Health Service Surveys 30. Two studies conducted among medical workers, teachers, factory workers and secondary students in Hong Kong and mainland China found that being male, married and having high quitting self-efficacy were associated with the intention to quit smoking 31 32.…”
Section: Introductionsupporting
confidence: 73%
“…Although Chinese smokers have expressed less interest in quitting smoking and received less assistance than their Western counterparts, the determinants of intentions to quit may be similar ( Feng et al, 2010 ;Qian et al, 2010 ;J. Yang et al, 2011 ;T.…”
Section: Introductionmentioning
confidence: 99%
“…The marginal probability distribution of the common feature showed the success rate was 36.40%. According to previous publications (Gallus et al, 2013;Hymowitz et al, 1997;Qian et al, 2010), the major reason for quitting smoking is individual illness or fear of being ill. Our data (73.77% smokers tried to quit smoking because of health problems) also verified the reason. The items of SAS includes many health questions, such as headache, fast heart beating, arms shake, fingers numbness, stomach aches and difficulty in breathing and so on (Zung, 1971).…”
Section: Discussionmentioning
confidence: 97%
“…Successful quitters refer to those who comply with the criterion of smokers, and had not smoked at all for 2 years or more continuously at the time of the survey (Qian et al, 2010). Failed smoking quitters refer to those who comply with the criterion of smokers, and ever quit but relapsed, or had not smoked at all for less than two years continuously at the time of the survey.…”
Section: Definitionsmentioning
confidence: 99%